The Framework On The Use Of Online Teaching And Learning Practices Among Secondary School Teachers: An Extension Of Technology Acceptance Model (Tam) - Izhar, Nurul Ashikin (2023)
This research aimed to extent TAM on secondary school teachers’ online teaching and learning practise. An Exploratory Sequential Design (ESD-mixed method) was used to conduct this research.